2005
DOI: 10.1148/radiol.2353040489
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Transhepatic Balloon Dilation of Portal Venous Stenosis in Patients with Living Donor Liver Transplantation

Abstract: Percutaneous transhepatic balloon dilation seems to be an effective method for treatment of portal venous stenosis after living donor liver transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
78
1
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(85 citation statements)
references
References 14 publications
1
78
1
5
Order By: Relevance
“…Finally, regarding the recurrence rate, this ranges between 0%-100%. Shibata et al [128] (2005) reported the most important series in the literature where the recurrence rate was 28.6%. Some authors recommend the use of anticoagulant therapy for the prevention of recurrent PVT [134] .…”
Section: Summary Of the Clinical Characteristics About Pvsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, regarding the recurrence rate, this ranges between 0%-100%. Shibata et al [128] (2005) reported the most important series in the literature where the recurrence rate was 28.6%. Some authors recommend the use of anticoagulant therapy for the prevention of recurrent PVT [134] .…”
Section: Summary Of the Clinical Characteristics About Pvsmentioning
confidence: 99%
“…Some authors consider the pressure gradient between the pre and poststenosis site. Wei et al [126] (2009) considered a gradient of > 5 mmHg to initiate treatment, while Shibata et al [128] (2005) used a significant gradient of > 3 mmHg. Other authors did not measure gradients if the stenosis was noted to be greater than 75% of the main portal vein diameter.…”
Section: Summary Of the Clinical Characteristics About Pvsmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 On the long-term results of this procedure, a recent study reported the patency of portal vein after balloon angioplasty for portal stenosis was 71.4% with a mean follow-up of 24.4 months. 10 For a residual significant stenosis or a recurrent stenosis within a few months after balloon angioplasty, the metallic stent placement should be considered. 11,12 However, there is a retransplantation case report about graft failure caused by portal thrombus after the placement of a portal vein stent for portal stenosis.…”
Section: 5mentioning
confidence: 99%
“…This finding is in accordance with previous reports on DDLT in adults and in children and on LDLT. [28][29][30][31] It shows that angioplasty is also effective after neoadjuvant radiotherapy, with the reservation that mostly multiple interventions were required and that the future course is less predictable in view of the progressive nature of late portal vein stenoses. Our own experience in patients without radiation is also favorable, although we favor the transjugular intrahepatic technique of portal vein angioplasty also for extrahepatic stenoses because it is likely to reduce the risk of intra-abdominal bleeding in comparison with the percutaneous transhepatic approach.…”
Section: See Article On Page 1372mentioning
confidence: 99%